2020
DOI: 10.1007/s12008-020-00739-9
|View full text |Cite
|
Sign up to set email alerts
|

Industry 4.0: smart test bench for shipbuilding industry

Abstract: Industry 4.0 promises to increase the efficiency of production plants and the quality of the final product. Consequently, companies that implement advanced solutions in production systems will have a competitive advantage in the future. The principles of Industry 4.0 can also be applied to shipyards to transform them into “smart shipyards” (Shipyard 4.0). The aim of this research is to implement an interactive approach by Internet of Things on a closed power-loop test bench equipped with sophisticated sensors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…After the equipment binding is completed, the data flows normally. The operation and maintenance data is generated according to the built-in rules of the Eq-DataModel: (1) The alarm rules are designed to monitor equipment by means of manual configuration rules, empirical knowledge base and data mining methods. Using big data analysis technology to obtain normal parameters of the equipment during normal operation, compared with real-time data.…”
Section: Implementation Methods Of the Equipment Data Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…After the equipment binding is completed, the data flows normally. The operation and maintenance data is generated according to the built-in rules of the Eq-DataModel: (1) The alarm rules are designed to monitor equipment by means of manual configuration rules, empirical knowledge base and data mining methods. Using big data analysis technology to obtain normal parameters of the equipment during normal operation, compared with real-time data.…”
Section: Implementation Methods Of the Equipment Data Modelmentioning
confidence: 99%
“…Problems such as lag in data collection, high processing difficulty, real-time monitoring and statistical difficulties are common. Therefore, it is the key goal of China's shipbuilding industry to promote digital shipbuilding and realize the intelligent transformation of key links [1]. A large number of construction equipment clusters, such as tire frames and welding machines, are necessary tooling equipment in the process of ship block construction, and their real-time operation status directly affects the efficiency and accuracy of block construction.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported improved system performance in terms of reduced noise and vibrations, increased efficiency of lubrication, reduced consumption, installation, and maintenance cost of the entire system [6,7]. In another study, Giallanza et al [8] used IR 4.0-based technologies to develop a smart shipyard for testing elevated power thrusters before installing them on high-speed crafts.…”
Section: Introductionmentioning
confidence: 99%